Идентификация восточноевропейских форм Syluaemus sylvaticus (Rodentia) и их географическое распространение - Загороднюк, И.В. (Вестник зоологии, 1993)
Type materials of Eastern European Sylvaemus ex. gr. «sylvaticus» are revised. A specimen of Sylvaemus sylvaiicus (Linnaeus, 1758) from Uppsala (Sweden) is here designated as neotype. Existing viewpoint that territory east of Dniper is occupied by S. uralensis (=microps) is shown to be erroneous. In contrary, S. sylvaiicus is shown to be a wide-range species in the region. The form «charkovensis» is a easternmost subspecies of S. sylvaiicus, not of S. uralensis as stated formerly. Syntypes of S. sylvaticus charkovensis M i g u I i n, 1936 were found in collection of the Zoological Museum of Schmalhausen Institute of Zoology (Kiev), and the lectotype is here designated. Examination of this materials and original data has shown the wide range of S. sylvaiicus in the eastern part of Ukraine except of the steppe zone and in adjacent regions of the Western Russia and Central Bielorusia, However, the species is rather rare over the region and its representation capacity in collections studied does not exceed 10 % among ail other Sylvaemus. A detailed distribution map is given, taxonomic history and identification of the eastern populations of S. sylvaticus are herewith considered.